Measuring Self-Reported Cognitive Function Following TBI: Development of the TBI-QOL Executive Function and Cognition-General Concerns Item Banks. Issue 5 (September 2019) - Carlozzi, Noelle E.; Tyner, Callie E.; Kisala, Pamela A.; Boulton, Aaron J.; Sherer, Mark; Chiaravalloti, Nancy; Tulsky, David S.
Abstract : Objective: To develop and calibrate new patient-reported outcome measures of cognitive concerns for individuals with traumatic brain injury (TBI). Setting: Five TBI model systems rehabilitation centers in the United States. Participants: Adults with medically confirmed history of TBI. Design: Cross-sectional survey in interview format. Main Measures: Traumatic Brain Injury-Quality of Life (TBI-QOL) Executive Function and TBI-QOL Cognition-General Concerns item banks. Results: A total of 569 adults with complicated-mild, moderate, or severe TBI completed preliminary item pools, which included 65 Executive Function items and 56 Cognition-General Concerns items. Confirmatory factor analysis supported the retention of 37 Executive Function and 39 Cognition-General Concerns items. Samejima's graded response model was used to estimate item parameters for associated computer adaptive test administrations, and informed the selection of corresponding static short forms. Data from an independent sample of 77 adults with complicated-mild, moderate, or severe TBI supported the test-retest reliability of these newly developed measures. Conclusion: The TBI-QOL Executive Function and Cognition-General Concerns item banks provide researchers and clinicians with reliable tools for assessing patient-reported post-TBI cognitive difficulties as part of the comprehensive TBI-QOL measurement system.